Near-ultraviolet continuum modeling of the 1985 April 12 great flare of AD Leo - Kowalski, Adam F. (Frontiers in Astronomy and Space Sciences, 2022)
White-light stellar flares are now reported by the thousands in long-baseline, high-precision, broad-band photometry from missions like Kepler, K2, and TESS. These observations are crucial inputs for assessments of biosignatures in exoplanetary atmospheres and surface ultraviolet radiation dosages for habitable zone planets around low-mass stars. A limitation of these assessments, however, is the lack of near-ultraviolet spectral observations of stellar flares. To motivate further empirical investigation, we use a grid of radiative-hydrodynamic simulations with an updated treatment of the pressure broadening of hydrogen lines to predict the $λ ≈ 1800-3300$ Å\ continuum flux during the rise and peak phases of a well-studied superflare from the dM3e star AD Leo. These predictions are based on semi-empirical superpositions of radiative flux spectra consisting of a high-flux electron beam simulation with a large, low-energy cutoff ($\gtrsim 85$ keV) and a lower-flux electron beam simulation with a smaller, low-energy cutoff ($\lesssim 40$ keV). The two-component models comprehensively explain the hydrogen Balmer line broadening, the optical continuum color temperature, the Balmer jump strength, and the far-ultraviolet continuum strength and shape in the rise/peak phase of this flare. We use spatially resolved analyses of solar flare data from the Interface Region Imaging Spectrograph, combined with the results of previous radiative-hydrodynamic modeling of the 2014 March 29 X1 solar ﬂare (SOL20140329T17:48), to interpret the two-component electron beam model as representing the spatial superposition of bright kernels and fainter ribbons over a larger area.